2018
DOI: 10.1155/2018/5397071
|View full text |Cite
|
Sign up to set email alerts
|

An Evacuation Route Model of Crowd Based on Emotion and Geodesic

Abstract: Making unconventional emergent plan for dense crowd is one of the critical issues of evacuation simulations. In order to make the behavior of crowd more believable, we present a real-time evacuation route approach based on emotion and geodesic under the influence of individual emotion and multi-hazard circumstances. The proposed emotion model can reflect the dynamic process of individual in group on three factors: individual emotion, perilous field, and crowd emotion. Specifically, we first convert the evacuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Bourgais et al [18] demonstrated a detailed process of applying cognitive architectures and social relations wherein they were able to integrate twenty emotions divided into three groups namely emotions related to events, emotions linked to other agents and emotions linked to actions performed by agents. Liu et al [19] developed an emotion model with three factors namely individual emotion, perilous field emotion, and crowd emotion illustrating the dynamic process of an individual in a group. Regardless of the individuals' personality (whether positive or…”
Section: Demonstrating Cognitive Aspects Affecting Evacuation Performancementioning
confidence: 99%
“…Bourgais et al [18] demonstrated a detailed process of applying cognitive architectures and social relations wherein they were able to integrate twenty emotions divided into three groups namely emotions related to events, emotions linked to other agents and emotions linked to actions performed by agents. Liu et al [19] developed an emotion model with three factors namely individual emotion, perilous field emotion, and crowd emotion illustrating the dynamic process of an individual in a group. Regardless of the individuals' personality (whether positive or…”
Section: Demonstrating Cognitive Aspects Affecting Evacuation Performancementioning
confidence: 99%
“…21 Liu et al proposed a perception driven emotional contagion model to simulate a rushing crowd in the evacuation. 22 Liu et al discussed the role of emotion and geodesic in evacuation navigation 23 and Xu et al proposed a crowd emotional contagion model with multiple risk sources 24 . With the development of technology and the popularity of surveillance equipment, it has become possible to validate a simulation model with computer vision techniques.…”
Section: Related Workmentioning
confidence: 99%
“…e evacuation decisionmaking problem is transformed into an evacuation route selection problem. It usually adopts the minimum cost maximum flow method, the queuing theory method, and the shortest path method [4][5][6][7]. Micromodels usually take individuals as objects.…”
Section: Introductionmentioning
confidence: 99%